The Urgence of Peaceful Settlement of State Administrative Disputes Through Mediation in State Administrative Courts - Hendri Darma Putra (LEGAL BRIEF, 2022)
The process or stages of examining State Administrative disputes at the State Administrative Court, both based on statutory regulations, as well as in judicial practice, do not include a reconciliation process between the litigants through mediation. This is different from the examination of civil cases in both the general court and religious courts, in which there is mediation between the litigants. Based on these problems, the purpose of this study is to analyze the urgency of peaceful settlement of state administrative disputes through mediation at the State Administrative Court, as well as its legitimacy. The research method used in this research is normative juridical, which is a method in normative legal research that analyzes secondary data, which is then analyzed qualitatively. The results of this research are as follows: Settlement of state administrative disputes peacefully through mediation in the Administrative Court State Enterprises are very important (urgent) as instruments to be applied to the procedural law of the State Administrative Court, so that the Procedural Law of the State Administrative Court is more comprehensive, and can fulfill the administration of justice which is simple, fast and low cost and provides greater access to the parties. in obtaining a settlement of state administrative disputes that fulfills a sense of justice, and the legitimacy of peaceful settlement of state administrative disputes through mediation at the State Administrative Court, it is necessary to make changes to the amendments to the Republic of Indonesia Law Number 5 of 1986 concerning Judiciary. State Administration, or at least amendments are made to the Regulation of the Supreme Court Number 1 of 2016 concerning Mediation Procedures in Courts, which are adjusted to the procedural law of the State Administrative Court, so that with a formal acknowledgment (legitimacy) peaceful settlement of state administrative disputes through mediation at the State Administrative Court, so that the amicable settlement of state administrative disputes through mediation at the State Administrative Court is recognized as valid.